2021
DOI: 10.3390/ph14090855
|View full text |Cite
|
Sign up to set email alerts
|

Inulin and Its Application in Drug Delivery

Abstract: Inulin’s unique and flexible structure, stabilization/protective effects, and organ targeting ability make it an excellent drug delivery carrier compared to other biodegradable polysaccharides. The three hydroxyl groups attached to each fructose unit serve as an anchor for chemical modification. This, in turn, helps in increasing bioavailability, improving cellular uptake, and achieving targeted, sustained, and controlled release of drugs and biomolecules. This review focuses on the various types of inulin dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 231 publications
(326 reference statements)
0
33
0
Order By: Relevance
“…Inulin is a natural fructan polysaccharide that can be found in a variety of plants. This compound is made of fructose and glucose units in a flexible backbone, which gives it considerable versatility [ 139 ]. Inulin has been widely used in drug delivery systems because of its rapid water solubility, low friability, and stability via oral administration [ 140 ], as well as a successful ocular permeation enhancer [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inulin is a natural fructan polysaccharide that can be found in a variety of plants. This compound is made of fructose and glucose units in a flexible backbone, which gives it considerable versatility [ 139 ]. Inulin has been widely used in drug delivery systems because of its rapid water solubility, low friability, and stability via oral administration [ 140 ], as well as a successful ocular permeation enhancer [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in Table 3 , it is shown that the sizes of NQs and NBs were influenced by the medium in which the nanoparticles were suspended; in an aqueous medium, a slight relaxation of inulin was reported, with pores generated in the matrix and a swelling of the sphere, due to the relaxation of the polymeric chains. This normally occurs in nanoparticles with inulin form a hydrophilic layer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structure and water dispersed phase hydrogels can encapsulate water-soluble drugs, though water-insoluble drugs can also be loaded. Macromolecular compounds or bioactive molecules, such as genes, peptides, proteins or even living cells or organs can also be entrapped in hydrogels [ 14 , 54 , 55 , 56 ]. Figure 17 [ 57 ] and Figure 18 [ 58 ] illustrate drug delivery of IHs.…”
Section: Current Trendsmentioning
confidence: 99%